PERANCANGAN VISUAL IDENTITY WARUNG SEAFOOD NASI SEK UNIANG PADANG BARU KOTA PADANG - UUN MAHATUL, Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The absence of a visual identity of the business of Nasi Sek Uniang Seafood Warung, based on observations of the current conditions, so it has not shown a visual identity that can be recognized by the public or consumers, in addition to business competitors Sek Uniang Rice Nasi Warung that developed in Padang. The purpose of this design is to create a visual identity in the form of information in the form of logograms and logotypes of the products of Sek Uniang Rice Nasi Warung.The design method used is the Glass Box method, the design carried out rationally and logically, starting from data collection, interviews and observations. The analytical approach used is the 5W + 1H analysis method (what, who, where, when, why, how) to find a solution to the problem at hand.The design of the main visual media identity of the Uniang Rice Seafood Stalls namely manual book, as well as supporting media namely, sign board, business card, menu list, hat, paper bag, invoice, clothes, apron, poster, x-banner, paper bag, mug, stickers, pins and stamps, which aim to strengthen the application of the main media.Keywords: Visual Identity, Brands, and Sek Uniang Rice Seafood Stalls.